Lipid Extraction Maximization and Enzymatic Synthesis of Biodiesel from Microalgae - I.M. Rizwanul Fattah (Applied Sciences, 2020)
Microalgae has received overwhelming attention worldwide as a sustainable source for energy generation. However, the production of biofuel from microalgae biomass consists of several steps, of which lipid extraction is the most important one. Because of the nature of feedstock, extraction needs special attention. Three different methods were studied to extract algal oil from two different algae variant, Chlorella sp. and Spirulina sp. The highest percentage oil yield was obtained by ultrasonication (9.4% for Chlorella sp., 6.6% for Spirulina sp.) followed by the Soxhlet and solvent extraction processes. Ultrasonication and Soxhlet extraction processes were further optimized to maximize oil extraction as solvent extraction was not effective in extracting lipid. For ultrasonication, an amplitude of 90% recorded the highest percentage yield of oil for Spirulina sp. and a 70% amplitude recorded the highest percentage yield of oil for Chlorella sp. On the other hand, for Soxhlet extraction, a combination of chloroform, hexane, and methanol at a 1:1:1 ratio resulted in the highest yield of algal oil. Afterward, the crude algae oil from the ultrasonication process was transesterified for 5 h using an immobilized lipase (Novozyme 435) at 40 °C to convert triglycerides into fatty acid methyl ester and glycerol. Thus, ultrasonic-assisted lipid extraction was successful in producing biodiesel from both the species.